Analyze It: Looking at Texts Critically. - Gosman, Gillian (Core skills., 2014)
Analyzing text is one of the greatest skills a young reader can develop. This book helps readers gain an understanding of what it means to read a text for information, recognize point of view, and search for evidence. Readers will also learn to recognize important components of texts, including the main idea, theme, and structure. Finally, readers will learn how to form and express their own opinions. "Quick Tip" boxes give opportunities to apply real-world advice to a situation. The book includes a glossary, table of contents, index, supplemental websites, and vivid visuals.